1995
DOI: 10.1074/jbc.270.9.4189
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Brain GO Isoforms Have Distinct γ Subunit Compositions

Abstract: The gamma subunit composition of the major bovine brain Go and Gi proteins (GOA, GOB, GOC, Gi1, and Gi2) was characterized using antibodies against specific gamma isoforms. Each of the purified G protein heterotrimers contained a heterogeneous population of gamma subunits, and the profiles of the gamma subunits found with Gi1, Gi2, and GOA were similar. In contrast, each GO isoform had a distinct pattern of associated gamma subunits. These differences were surprising given that all three alpha O isoforms are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
49
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 51 publications
5
49
1
Order By: Relevance
“…An ␣ oC -like protein has been observed by a large number of groups (21)(22)(23)(27)(28)(29)(30). Recently, we have found that it is a relatively abundant protein in brain, constituting about a third of the G o of cerebral cortex.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…An ␣ oC -like protein has been observed by a large number of groups (21)(22)(23)(27)(28)(29)(30). Recently, we have found that it is a relatively abundant protein in brain, constituting about a third of the G o of cerebral cortex.…”
mentioning
confidence: 99%
“…Three of the isoforms, ␣ oA , ␣ oB , and ␣ oC , are purified associated with ␤␥ dimers as G oA , G oB , and G oC , while ␣ oD , an inconsistently observed ␣ o isoform, is not. Immunological evidence and peptide mapping suggest that ␣ oB and ␣ oD are protein products of the ␣ o2 mRNA, whereas ␣ oA and ␣ oC are translated from the ␣ o1 mRNA (23)(24)(25)(26). The functional significance of these different ␣ o isoforms is not yet clear, but the G oA , G oB , and G oC heterotrimers each contain a different assortment of ␤␥ dimers (23).…”
mentioning
confidence: 99%
See 3 more Smart Citations